Development of Training Program for Persons in Community: Healthy Foods for Monks - Joomsil, Taweesup (Journal of The Royal Thai Army Nurses, 2023)
This research and development had aimed to develop a training program for healthy food for monks and test and assess the effectiveness of the program in terms of knowledge, attitudes and behaviors of healthy food offered to monks of program participants. The research was divided into 4 phases. These were including Situation Analysis, Design and Development, Implementation and Evaluation using the interview method with interview form to collect in the sample aged 45-79 years of 99 people. The samples were selected using the Cluster Sampling method, which was divided into 3 groups: 1)The situation analysis phase sample group of 52 people provided qualitative data by interview. 2)The design and development phase samples, 17 people who participated in the program developed for the first time and 3)The Implementation phase samples, 30 people who participated in the second developed program and a comparative analysis was conducted for the difference in mean scores of the samples between before and after participating in the program using the Wilcoxon signed-rank test at a significant level at statistical .05. Results found: 1) The complete healthy food training program for offering to monks has a total duration of 8 weeks in 8 learning plans. These were Experience 1 time, Critical reflection 1 time, Reflective discourse 1 time and Action 5 times. Design activities by applying the Transformative Learning theory with data from community situation analysis and literature review. and 2)The effectiveness of the program trial was found After participating in the program, the sample group had average knowledge scores, attitudes and behaviors regarding healthy food for monks that were significantly higher than before participating in the program (p<.05) Suggestions from research are Community health services can apply the program to the community to encourage people in the community to have a level of knowledge, attitudes and behaviors of offering healthy food to monks are increasing.